Strategies for Student Belonging : The Nexus of Policy and Practice in Higher Education. - Mahoney, Brendan; Kumar, Jennifer; Sabsabi, Mohammed (Student Success v.13 n.3 p.54-62 https://doi.org/10.5204/ssj.2479, 2022)
This practice report, framed within transition pedagogy (Kift et al., 2010), seeks to offer suggestions to assist higher education educators and administrators to develop and apply policies to foster student belonging. The authors of this article are employed at an Australian university which offers alternative pathways for students to enter a mainstream university degree. The authors were part of a project sub-committee responsible for reviewing literature on the definition of, and approaches to, belonging and writing a report with suggestions to enhance student engagement and progression. The report concluded that belonging should be a "whole-of-institution" approach (TEQSA, 2020) where all aspects of a student’s journey are considered when developing and applying student success strategies. This practice report culminates past studies and offers belonging enhancing teaching advice, policy suggestions and learning tools to strengthen connections between students and the higher education institutions in which they are enrolled. [Author abstract]